2015
DOI: 10.1039/c5py00919g
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization-induced self-assembly driving chiral nanostructured materials

Abstract: To prepare chiral nanostructures coated with bioactive molecules, a side-chain amino acid containing macromolecular chain transfer agent (macroCTA), poly(Boc-L-alanine methacryloyloxyethyl ester) (PBLAEMA), has been used as the steric stabilizer for the reversible addition-fragmentation chain transfer (RAFT) mediated dispersion polymerization of benzyl methacrylate (BzMA) in methanol at 65°C. Gel permeation chromatography (GPC) analysis confirmed an efficient and well-controlled block copolymerization. A full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 76 publications
1
65
1
2
Order By: Relevance
“…Polymerization‐induced self‐assembly is a convenient way of making a myriad of macromolecular nanoobjects depending upon the solvophilic/solvophobic volume ratio by using living radical polymerizations. A full spectrum of morphologies spanning spherical micelles, worm‐like micelles, fibers, vesicles, etc., could be attained by changing reaction parameters (Figure ) …”
Section: Self‐assembly Of Amino‐acid‐derived Polymeric Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization‐induced self‐assembly is a convenient way of making a myriad of macromolecular nanoobjects depending upon the solvophilic/solvophobic volume ratio by using living radical polymerizations. A full spectrum of morphologies spanning spherical micelles, worm‐like micelles, fibers, vesicles, etc., could be attained by changing reaction parameters (Figure ) …”
Section: Self‐assembly Of Amino‐acid‐derived Polymeric Architecturesmentioning
confidence: 99%
“…A full spectrum of morphologies spanning spherical micelles, worm-like micelles, fi bers, vesicles, etc., could be attained by changing reaction parameters ( Figure 6 ). [ 118 ] In addition, we have synthesized different side-chain dipeptidebased homopolymers and their corresponding block copolymers with mPEG 2k . Self-assembly of those amphiphilic block copolymers and double hydrophilic block copolymers were investigated in detail.…”
Section: Self-assembly Of Amino-acid-derived Polymeric Architecturesmentioning
confidence: 99%
“…Studying chiral transfer phenomenon can provide guidance for the directional design of chiral nanostructure materials. Self‐assembly is an ideal way to prepare chiral materials . H‐bonding plays a major role in the process of chirality transfer .…”
Section: Introductionmentioning
confidence: 99%
“…Selfassembly is an ideal way to prepare chiral materials. 29,30 H-bonding plays a major role in the process of chirality transfer. 31,32 Wei et al reported that chirality information can be transferred from conjugated molecules to structures using π-conjugated molecules as functional building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different polysaccharide‐based functional polymeric nano‐particles were reported through PISA process . We also have used a side‐chain alanine containing methacrylate polymer as a steric stabilizer and polymerization control agent for RAFTDP of benzyl methacrylate (BzMA) to obtain diverse sets of block copolymer nano‐objects in methanol …”
Section: Introductionmentioning
confidence: 99%